A Rare Case of A Primary Squamous Cell Carcinoma of the Rectum - Hajri, Mohamed; Ferjaoui, Wael; Talbi, Ghofrane; Omrani, Sahir; Baccouche, Seifeddine; Gharbi, Lasaad; Mestiri, Hafedh; Bayar, Rached; Bacha, Dhouha; Slama, Sana ben (International Journal of Human and Health Sciences (IJHHS), 2022)
Squamous cell carcinoma (SCC) of the gastrointestinal tract is uncommon and usually involves the esophagus or the anal canal. More than 90% of tumors arising the colorectal region are adenocarcinomas. SCC is exceedingly rare accounting for 0.1 to 0.25 % of all colorectal malignancies. Due to its rarity and the lack of literature in this regard, and etiology and pathogenesis also remain obscure. However, we report here a rare case of squamous cell carcinoma of the rectum in a 68-year-old womanwith no known comorbidities except a history of asthenia, loss of appetite and change in bowel habits for the last three months with 10 kg of weight loss over the last two months. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 335-337